How united states immigration laws enable modern slavery - Urrelo Huapaya, Giuliana Belissa (2018)
Human trafficking is arguably one of the most profitable transnational crimes today. Although slavery was abolished in the United States with the passage of the Thirteenth Amendment in 1865, the practice of selling and exploiting the will of humans continues to occur. In fact, in 2000, the United States enacted legislation, the law Victims of Trafficking and Violence Protection Act of 2000, which prohibits both sex trafficking and labor trafficking. Despite concerted efforts to combat human trafficking, the trade in person continue to grow and although the Trafficking and Violence Protection Act is an improvement over past policies, only a fraction of the estimated victims are being reached and assisted with the purpose provide services that would address their needs. This article will explore the world’s trafficking problem addressing the human trafficking in the United States and how the existing immigration policies allow trafficking to persist in the Unites States.